Kepastian Hukum Terkait Pembagian Harta Waris Bagi Ahli Waris Perempuan dalam Masyarakat Hukum Adat Batak Toba melalui Surat Keterangan Waris - Jessica, Graciella Ratna; Meliyana Yustikarini (LPPM Universitas Ekasakti Padang, 2024)
In the provisions of Batak Toba Customary Law, especially Batak Toba Customary Inheritance Law, women are relatively weak legal subjects. As a result of the patrilineal kinship system adopted by the Batak Toba indigenous community, women have limited rights, inversely proportional to men. As subjects who are often considered 'passengers' in a family, women in the Batak Toba indigenous community face direct discriminatory treatment in the eyes of the Batak Toba customary law itself. However, along with the pace of development of the times, gender-based discrimination in various aspects is no longer considered relevant. Referring to Article 17 of Law No. 39 of 1999 concerning Human Rights and the Jurisprudence of the Indonesian Supreme Court No. 179K/Sip/1961, women's inheritance rights are equal to men. Where customary laws that are no longer able to adjust to the development of community life, such as not recognizing the position of women as equal to men, cannot be maintained. Departing from this, women in the Batak Toba indigenous community have a legal protection to be able to defend their rights and position in the eyes of the law to be equal to men. Regarding the issue of inheritance rights, women in the Batak Toba traditional community can take care of making a Certificate of Inheritance.